Gender Disparities in Self-Presentation on WeChat Moments - Zhang Xinyuan (SHS Web of Conferences, 2024)
This study delved into the relationship between gender and self presentation in WeChat Moments, and analyzed gender patterns and differences through questionnaire data. Using Erving Goffman’s drama theory, self presentation in WeChat Moments is viewed as an online performance, in which users play their own roles and carefully manage their online image. WeChat Moments serve as an inclusive space where users of all genders can express themselves and participate in social networks. Research has found that regardless of gender, both male and female users actively participate in posting behavior on WeChat Moments. Although male posting frequency is slightly higher, this difference is not statistically significant. The survey also found that gender has no significant impact on the composition of personal social networks and unique content creation in WeChat Moments. This study provides important insights into the role of gender in social media usage and self presentation, enriching our understanding of digital social platforms.